Загальний аналіз конструкцій нагнітачів високообертових двигунів на прикладі нагнітачів повітря - Прокопенко, Микола Вікторович; Ткачук, Микола Анатолійович; Гречка, Ірина Павлівна (Таврійський державний агротехнологічний університет ім. Д. Моторного, 2021)
Наведено загальний оглядовий аналіз конструкцій нагнітачів високообертових двигунів на прикладі нагнітачів повітря. Розглянуто особливості роботи, переваги та недоліки різних за принципом дії нагнітачів. Наведено принципові схеми таких нагнітачів і проаналізовано їх конструктивні особливості з точки зору використання у форсованих швидкохідних двигунах бронетанкової техніки. Визначені основні вимоги щодо конструкцій нагнітачів повітря у двигунах бронетанкових машин. Доведена актуальність не тільки удосконалення цих конструкцій, а й урахування особливостей моделей та умов експлуатації двигуна, з одного боку, і бронетанкової машини, – з іншого. Більш детально розглянуто особливості роботи відцентрових компресорів, як таких, що найчастіше використовуються у форсованих двигунах бронетанкових машин. Розглянуто основні конструкції нагнітачів, які використовуються у таких двигунах. Наведено рекомендації щодо досягнення надійності роботи елементів нагнітача в умовах форсування двигуна.

The article discusses the main stages and directions of development of new technologies that allow manufacturers to modernize equipment and create more powerful tractors. In modern models, the latest achievements of mechanical engineering and electronics are combined. At the same time, the mechanical part of an agricultural machine is much cheaper than all electronic novelties. What is the advantage of high-tech tractors. In recent years, such trends have been noted in tractor construction as an increase in the model range of manufactured tractors, an increase in their power, improvement of engines, fuel equipment, filtration and air intake systems, taking into account environmental requirements in the design, improvement of conventional and introduction of continuously variable transmissions, as well as improvement of hydraulic equipment: increase in pressure and an increase in the number of operations performed by the hydraulic mechanism; expanding the use of electronics, automation of operations and processes; increased use of sprung bridges and their improvement; expanding the use of polymers and new materials; creating comfortable and safe working conditions. Tractors must meet certain operational requirements based on scientifically sound properties and performance. These requirements include, above all, ensuring high productivity and efficiency, the implementation of the whole complex of agricultural work in high quality, in the best agronomic terms. The agro-ecological requirements related to the pollution of the atmosphere with harmful components contained in the exhaust gases of engines and the impact of the running gear of these machines on the ground are important.
General analysis of charger structures of high–speed engines by example air supplies
Keywords: нагнітач повітря для високообертових двигунів; бронетанкова техніка; модель експлуатації двигуна; відцентровий компресор; надійність елементів нагнітача; air blower for high-speed engines; armored vehicles; engine operation model; centrifugal compressor; reliability of blower elements